DISTRIBUTION OF R-FACTORS IN GRAM NEGATIVE BACTERIA - Sh.Hakimi; M.Sigaroodi; M.Mohammadi; B.Ghorayshi; S.Mahajer (Tehran University of Medical Sciences, 1981)
A total number of 259 gram negative bacteria (entero-bacteria) isolated during the years 1973-1974 was examined. These strains were isolated from sick children referred and or hospitalized in a children hospital in Tehran. The strains consisted of ; 131E.coli, 52 Salmonella, 40 Klebsiella, 18 Shigella, 13 Proteus, 3 Enterobacter and 2 Citrobacter. Sensitivity tests were performed according to the method of Kerby and Bauer. It was shown that 59% of these bacteria were drug resistant with the majority of the strains carrying resistances to two or more drugs (multiple resistances). Drug resistance was found in 78.9% of Salmonelleae, 77.7% of Shigelleae, 55.5% of Escherichieae, 52.5% of Klebsielleae and 61.5% of Proteae. Further studies have shown that the majority of these resistances were mediated by R-factor. None of the S.typhi strains so far tested was found to be resistant to any of the antimicrobial drugs used in this study.